Inclusive Education : Perception of an Educational Community - Vallejos Garcías, Viviana; Castro Durán, Lilian (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this study is to evaluate the perception of educational inclusion in its dimensions of policies, practices and culture of directors, teachers and education assistants, considering the role and gender variables, in secondary schools in the eighth region. of the Biobío of Chile. The methodology is quantitative and descriptive, with a non-experimental transactional design, the sample is made up of 346 professionals. The general results show a very favorable perception towards the inclusive practices dimension, both in the role variable for managers and in gender for women.